Study on mechanical and thermal behavior of the lightweight aggregate geopolymer concrete (LWAGC) using fly ash - Omar A.K.A. Abdulkareem (School of Materials Engineering, University Malaysia Perlis, 2014)
Geopolymers are part of polymer science, chemistry and technology that forms one of the major areas of materials science as well as in producing of new green materials that can alternative cementitious material to ordinary Portland cement (OPC) due to their brilliant environmentally-friendly benefits. Structural lightweight aggregate concrete LWAC has been found in the available literature. This thesis presents the synthesis process procedures of a structural lightweight aggregate geopolymer concrete (LWAGC) system based on the American Concrete Institute (ACI) committee 211-standard (ACI 211.2). The LWAGC was prepared by alkali activation of a Fly Ash (FA) consist of sodium silicate (Na2SiO3) and sodium hydroxide solution (NaOH). The geopolymer paste binder was used to bind a mixture of natural aggregates and lightweight expanded clay aggregate (LECA). The physical, mechanical, microstructural and thermal properties of the prepared LWAGC before and after being exposed to elevated temperatures ranged of 100-800 C were extensively investigated through this work. The physical and mechanical results of the unexposed LWAGC to heating temperatures of 100 C to 800 C showed that it comply the ACI 211.2 standard for designing a structural LWAGC based on the geopolymerization technology. The fresh LWAGC mixture was recorded a slump value of 95 mm, while the hardened LWAGC possessed a compressive strength and volume of 18.86 MPa and 1438.70 kg/m3, respectively at 28 days. These classify it as a structural LWAGC which can be used as a construction material. The unexposed LWAGCs were also showed a continuous strength gaining versus aging times up to 1 year. The optimizing of Activator/FA mass ratio used in the LWAGC preparation has been also investigated at a range of 0.3-0.7, which revealed that the Activator/FA mass ratio proposed by the ACI 211.2 standard of 0. 59 was the optimum activator content as it provide the desired workability and the highest compressive strength than other tested ratios. The microstructural and physical analysis showed that, the thermal properties of LWAGC improved significantly after been exposed to elevated temperature of 400 C, 600 C and 800 C. The mechanical, physical and microstructural results showed the aggregates (sand/sand + LWA) significantly improved the fire resistance of FA geopolymer mortar and LWAGC. The strength of the LWAGC increased after exposed to 100 C to 300 C. These materials are excellent for the applications up to 300 C.